Noninvasive Urine Biomarker Lateral Flow Immunoassay for Monitoring Active Onchocerciasis - Shirey, Ryan J. (ACS Infect Dis, 2018)
[Image: see text] The parasitic disease onchocerciasis is the second leading cause of preventable blindness, afflicting more than 18 million people worldwide. Despite an available treatment, ivermectin, and control efforts by the World Health Organization, onchocerciasis remains a burden in many regions. With an estimated 120 million people living in areas at risk of infection, efforts are now shifting from prevention to surveillance and elimination. The lack of a robust, point-of-care diagnostic for an active Onchocerca infection has been a limiting factor in these efforts. Previously, we reported the discovery of the biomarker N-acetyl-tyramine-O-glucuronide (NATOG) in human urine samples and its ability to track treatment progression between medicated patients relative to placebo; we also established its capability to monitor disease burden in a jird model. NATOG is a human-produced metabolite of tyramine, which itself is produced as a nematode neurotransmitter. The ability of NATOG to distinguish between active and past infection overcomes the limitations of antibody biomarkers and PCR methodologies. Lateral flow immunoassay (LFIA) diagnostics offer the versatility and simplicity to be employed in the field and are inexpensive enough to be utilized in large-scale screening efforts. Herein, we report the development and assessment of a NATOG-based urine LFIA for onchocerciasis, which accurately identified 85% of analyzed patient samples (N = 27).